An Unusual Cause of Cardiac Tamponade during Cardiac Catheterization Study. (17th September 2014) - Das, Deepanwita; Datta, Monalisa; Dey, Somnath; Parida, Jyotiranjan; Kumar, Rupesh; Pande, Arindam
Abstract : Introduction. Catheter-based diagnostic and therapeutic procedures are rapidly advancing. However, catheter related complications sometimes become life threatening. Cardiac tamponade is a rare but serious complication of this procedure. We have summarized one cardiac tamponade pejoration due to secondary coronary vessels laceration by the implanted pericardial drainage. Case report . A 4-year-old baby having Tetralogy of Fallot was posted for diagnostic catheterization study. Patient was induced with sevoflurane and spontaneous respiration was maintained. After catheter insertion to RV, dye was injected through the catheter which rapidly spread into the pericardial cavity indicating right ventricle perforation. Immediately, blood was aspirated under transthoracic echocardiographic guidance and hemodynamics started improving. For the provision of quick access to aspirate further collection, an intrapericardial sheath was inserted after multiple attempts. Patient's condition started deteriorating again. TTE revealed again some collection and it was increasing gradually. On exploration, it was found that there was continuous bleeding from a lacerated epicardial vessel which contributed to the pericardial collection leading to further tamponade effect. This second iatrogenic injury complicated the management of the first iatrogenic cardiac perforation and, thereby, created a life-threatening situation which needed immediate surgical exploration. Discussion . Usual cause of tamponade after right ventricular perforation is bleeding from the RV, but in our case the second tamponade was not due to bleeding from the RV, but was rather from new laceration injury of epicardial vessels which was remained undiagnosed till exploration.